Application value of strain elastography in testicular injury assessment after torsion - Zhou, Jiehong; Peng, Chihan; Zhu, Xiaoxia; Yao, Wenqing; Luo, Yan; Yang, Lulu (Frontiers in Pediatrics, 2024)
Aim: To evaluate the capability of strain elastography (SE) in assessing testicular injury degrees after torsion.Material and methods: Fifty rabbits were divided into four groups according to the different degrees of testicular torsion (TT) at 0 • , 180 • , 360 • and 720 • . For each animal, according to the tissue stiffness distribution, SE score and strain ratio (SR) were obtained. With the histopathological results as the reference, the correlation coefficients of apoptotic index and SE score or SR were calculated, and the receiver operating characteristic (ROC) curves were created to assess the capability of SE in assessing testicular injury degrees.Results: A significant positive correlation was found between apoptotic index and SE score, as well as the SR, the corresponding correlation coefficient was 0.70 (<0.001) and 0.68 (P =0.001), respectively. The areas under the ROC curves (AUCs ) of SE score and SR for identifying ischemia/hypoxia injury were found to be 0.81(95% CI, 0.71-0.93) and 0.73 (95% CI, 0.60-0.86), respectively. In identifying irreversible damage, the AUCs were 0.69 (95% CI, 0.56-0.83) and 0.71(95% CI, 0.59-0.84) for SE score and SR, respectively.Conclusions: SE scores exhibited good diagnostic capability for detecting ischemia/ hypoxia injury after TT. In early identification of severe injury/necrosis following TT, SE demonstrated some value, but not ideal.